SISTEM PEMIDANAAN ANAK SEBELUM DAN SESUDAH BERLAKUNYA UNDANG-UNDANG NOMOR 11 TAHUN 2012 - Fransiska Novita Eleanora (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2016)
Children are the future generation so to note what became of his rights in the protection and maintenance and always puts the best interests of each child, so the child can grow over time and evolve. This is done in line with children as victims or perpetrators, where given a specificity or differences with penalties against adults so as not to affect the psychological and psychiatric the children. Formulation of the problem is the system of punishment How children and child rights protection According to Law no. 11 in 2012. The method of research is the study of literature, by examining the existing literature related to Child Punishment. The goal is to determine whether the presence of Punishment System imposed by Law. 11 The year 2012 may provide a deterrent effect as well as the recovery of the child as a criminal and how the difference prior to the act, especially in a criminal case anyway and the result is that Law. 11 The year 2012 gives more freedom in settling disputes out of court child melaliu diversion and restorative justice